(untitled) (Orinoquia, 2021)
The way science communicates to the general population has always been a challenge, mainly because it is loaded with specialized technical information, making it difficult to connect with the target audience of the message. That is the problem since the population must appropriate the knowledge to make healthy decisions for their lives. Climate change is one of the areas that are most difficult to connect with people’s daily lives. Therefore, the objective was to design pleasant communicative pieces about climate change and health from an informal and day-to-day language within the framework of two research projects in climate change and its relationship with health. Two projects were carried out, one open to the entire academic community of the Universidad del Magdalena; the other focused on the student population of the same university’s health programs. Communicative pieces, infographic-style, and templates designed in both projects, derived from a conceptual review and scientific articles. These communicative pieces were widely disseminated through different media, and the scope and clarity of the information we explored by different strategies (surveys, social media, and others). We found that presenting the information graphically and with striking colors attracted the attention, especially of the young public, who reacted quickly to the contents, understood the messages, and learned about aspects they did not know. Some of the pieces were disclosed in local media (Example: https://www. seguimiento.co/magdalena/con-infografias-unimagdalena-sensibiliza-sobre-el-cambio-climatico-38123; https://www.hoydiariodelmagdalena.com.co/archivos/392786) Adapting technical and scientific knowledge to populations in a friendly, transparent, and inclusive way is only the first step to having more and better-informed citizens that can face the determinants of health to protect and maintain the health of their communities. The new generations require different forms of communication focused on images, more playful and original. The information is only the starting point to involve the populations in organizational and participatory actions to propose adaptive and mitigation alternatives related to health protection.